Ratings versus market-based measures of default risk in portfolio governance - Löffler, Gunter (Journal of Banking & Finance, 2004)
This paper assesses whether ratings or market-based credit risk measures are more suitable for formulating portfolio governance rules. Such rules, which consist of buy and sell restrictions, are commonly used in investment management. Based on data from 1983 to 2002, it is not evident that one of the two measures is superior. The relative power of the two measures in predicting defaults depend on the investor’s investment horizon and risk appetite. The results support the agencies’ claim that their policy of reducing rating volatility, which builds on the though-the-cycle approach and the avoidance of frequent rating reversals, is beneficial to bond investors. The results also suggest that widely used statistical measures of rating quality may be insufficient to judge the economic value of rating information in specific contexts.